Tuberculosis in childhood and adolescence: a view from different perspectives - Tony T. Tahan; Betina M.A. Gabardo; Andrea M.O. Rossoni (Elsevier, 2020)
Objective: To describe the epidemiological situation of tuberculosis in children under 19 years of age in Brazil and to review the latest publications on disease risk, diagnosis, treatment, and prevention. Source of data: Notifiable Diseases Information System (2018), World Health Organization estimates, and PubMed articles selected using the descriptor "Tuberculosis," delimited by type of study, period, age, and language. Synthesis of data: In 2018, in Brazil, 9.4% of notifications were in children under 19 years. The pulmonary form predominated in 80.1% of the cases. The cure rate was 76.8%, lethality was 0.8%, and abandonment was 10.4%. The prevalence of drug-resistant tuberculosis (2011-2016) was 0.5%. It has been found that the risk of disease can reach up to 56% in children under 5 years, influenced by helminth co-infections, malaria, chronic viral infections, live attenuated virus vaccines, and hypovitaminosis D. Exposure to a bacilliferous patient for periods shorter than 30 minutes is sufficient for the development of infection and/or disease. In Brazil, microbiological screening is recommended, but the use of the scoring system, modified in 2019, has been maintained. Studies on infection detection have supported the use of the tuberculin skin test. In the treatment, the great advance was the introduction of dispersible formulations, adjustment of the recommended doses, and shortened regimens for latent infection. Several vaccine studies (stages 1-3) are ongoing, but no BCG-licensed substitute has been implemented yet. Conclusions: There has been progress in treatment, but major challenges need to be overcome to improve diagnosis, monitoring, and outcome of cases, aiming to eliminate tuberculosis. Resumo: Objetivo: Descrever a situação epidemiológica da tuberculose nos menores de 19 anos no Brasil e revisar as últimas publicações sobre risco de adoecimento, diagnóstico, tratamento e prevenção. Fonte dos dados: Banco de notificação Brasil (2018), estimativas da Organização Mundial da Saúde e artigos do PubMed selecionados pelo descritor Tuberculosis, delimitaram-se tipo de estudo, período, idade e língua. Síntese dos dados: Em 2018, no Brasil, 9,4% das notificações foram nos menores de 19 anos. Predominou a forma pulmonar em 80,1% dos casos. A taxa de cura foi de 76,8%, letalidade 0,8% e abandono 10,4%. A prevalência de tuberculose drogarresistente (2011 a 2016) foi 0,5%. Encontrou-se que o risco de adoecimento pode chegar até 56%, nos menores de cinco anos, influenciado por coinfecções com helmintos, malária, infecções virais crônicas, vacinas de vírus vivos atenuados e hipovitaminose D. A exposição ao doente bacilífero por períodos menores de 30 minutos é suficiente para o desenvolvimento de infecção e/ou doença. No Brasil, recomenda-se a pesquisa microbiológica, porém mantem-se o uso do Sistema de Pontuação, modificado em 2019. Estudos sobre detecção da infecção respaldaram o uso da prova tuberculínica. No tratamento, o grande avanço foi a introdução das formulações dispersíveis, adequação das doses preconizadas e esquemas encurtados para infecção latente. Vários estudos de vacinas (fases de 1 a 3) estão em andamento, mas ainda sem substituto licenciado para a BCG. Conclusões: Observaram-se progressos no tratamento, porém ainda há grandes desafios para melhorar o diagnóstico, monitoramento e desfecho dos casos em busca da eliminação da tuberculose. Keywords: Child, Diagnosis, Treatment, Prevention, PALAVRAS-CHAVE: Criança, Diagnóstico, Tratamento, Prevenção